THE EFFECT OF CUSTOMIZATION STRATEGY BEHAVIOR ON COMPANY PERFORMANCE THROUGH ACCOUNTING INFORMATION SYSTEMS BROAD SCOPE MANAGEMENT AND AGREGATION - Raza, Hendra (RADJA PUBLIKA, 2022)
This study aims to determine the effect of customization strategy behavior on company performance through a wide-ranging and aggregation management accounting information system at the Arasco Coffee Powder Factory, Bireuen Regency. The data used in this study is primary data with the sampling technique used is the total sampling technique. The sample used is 37 people. The method used to analyze the relationship between the independent variable and the dependent variable is multiple linear regression. The results showed that the customization strategy had an effect on company performance through a broad scope of management information system at the Arasco Coffee Powder Factory, Bireuen Regency.